Pengaruh Lingkungan Fisik Sekolah Terhadap Motivasi Belajar dan Perilaku Siswa di Sekolah Dasar - Nurkhalifah; Haifaturrahmah; Nursina Sari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The physical condition of a school plays a crucial role in supporting a conducive learning process, particularly at the elementary school level. A comfortable, clean, well-organized physical environment, supported by adequate facilities, can influence students' motivation to learn and their behavior. This community service activity was conducted at an elementary school with the aim of raising awareness among teachers, students, and school officials regarding the importance of managing the school's physical environment as a supporting factor in fostering positive behavior and student motivation to learn. The methods used included observing school conditions, providing outreach, and providing assistance in reorganizing the physical environment of classrooms and learning areas. The results of the activity showed increased student enthusiasm for learning, improved discipline, and a higher enthusiasm for learning after the school environment was properly organized. Therefore, optimal management of the school's physical environment can be an effective strategy in supporting increased learning motivation and fostering positive behavior in elementary school students.